Scattering of scalar waves by many small particles - Ramm, Alexander G. (My University, 2011)
Formulas are derived for solutions of many-body wave scattering problems by small particles in the case of acoustically soft, hard, and impedance particles embedded in an inhomogeneous medium. The limiting case is considered, when the size a of small particles tends to zero while their number tends to infinity at a suitable rate. Equations for the limiting effective (self-consistent) field in the medium are derived.
Keywords: Acoustic impedance; Acoustic wave scattering; Inhomogeneous media; Many-body problems